Intertextual-Based Chemistry Learning in Salt Hydrolysis Concept to Improve Students' Science Process Skills - Izzatul A'qidah; Setia Rahmawan (Didaktika: Jurnal Kependidikan, 2024)
Teaching with multiple representations provides a rich context for helping students overcome difficulties in understanding chemical concepts. Learning models such as POE (Predict-Observe-Explain) can enhance students' science process skills. The purpose of this study was to determine the effectiveness of the POE model in learning salt hydrolysis to improve high school students' science process skills. The method used was quantitative, with questionnaires for data collection. The research findings are as follows: (1) students are more interested in the practicum method, (2) many students do not understand the equipment used in the practicum, and (3) many students have science process skills scores lower than their cognitive scores. Therefore, science process skills must be applied to students.